The other side of COVID-19: A cross-sectional study on mental health in a sample of Italian nurses during the second wave - Renzi, Erika; Imeshtari, Valentin; Masud, Dima; Baccolini, Valentina; Migliara, Giuseppe; Gasperini, Giulia; De Vito, Corrado; Marzuillo, Carolina; Villari, Paolo; Massimi, Azzurra (Frontiers in Psychiatry, 2023)
The COVID-19 pandemic has led to a drastic increase in the workload of healthcare professionals, particularly nurses, with serious consequences for their psychological well-being. Our study aimed to identify demographic and work-related factors, as well as clinical predictors of post-traumatic stress disorder (PTSD) and generalized anxiety disorder (GAD), in nurses employed during the COVID-19 pandemic. We carried out a cross-sectional study between December 2020 and April 2021 of nurses employed during the COVID-19 second wave (October - December 2020). We evaluated PTSD and GAD using two validated questionnaires: i) the Impact of Event Scale – Revised (IES-R); and ii) General Anxiety Disorder –7 (GAD-7). Overall, 400 nurses, whose mean age was 34.3 years (SD ± 11.7), were included in the study. Most were female (78.5%), unmarried (58.5%) and employed in the central (61.5%) regions of Italy. A total of 56.8% of all participants had clinical predictors of PTSD, recording a median IES-R score (IQR) of 37.0 (22.0, 51.0) (range 1-84; cut-off >33 for PTSD). Furthermore, 50% of respondents reported moderate-to-severe symptoms consistent with GAD, recording a median GAD-7 score (IQR) of 9.5 (6.0-14.0) (range 0-21; cut-off >10 for GAD). Multivariable analysis showed that moderate-to-severe GAD (aOR = 4.54, 95% CI: 2.93 - 7.05), being employed in the critical care area (aOR = 1.74, 95% CI: 1.01 - 3.00) and being female (aOR: 1.88, 95% CI: 1.09 - 3.22) were significantly associated with the presence of clinical predictors of PTSD. The levels of PTSD symptoms and anxiety among nurses were high during the pandemic. PTSD and GAD represent a public health problem that should be addressed in the post-pandemic period. Healthcare organizations need to activate specific support and rehabilitation networks and programs for healthcare professionals employed during the COVID-19 pandemic.